Eksplorasi Etnomatematika pada Bangunan Masjid Agung Mataram Kotagede - Bagas Sanyoto; Dafid Setiana; Denik Agustito (Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to explore the concept of learning mathematics at The building of the Great Mosque of Mataram, Kotagede, to translate it into mathematics in schools and to encourage students to preserve and protect cultural heritage. The method in this research is a qualitative research method with an ethnographic approach. The data collection technique is done by using observation, interview and documentation methods. The results showed that there are quite a lot of mathematical concepts in the building of the Great Mataram Kotagede Mosque. In this research, the researcher found several flat shapes and space shapes, among others; triangle, rectangle, trapezoid, square, right triangle, tube, pyramid, cube, and cuboid.